Sanditon. Season two [videorecording (DVD)] - Williams, Rose, 1994-; Ashfield, Kate; Ays, Maxim, 1998-; Blake, Frank (Actor); Clarke, Crystal (Actor); Convery, Turlough; Eldon, Kevin, 1960-; Fox, Jack, 1985-; Graham, Rosie; Lloyd-Hughes, Ben, 1988-; McDade, Sandy; Mitchell, Flora (Actor); et al. (PBS, 2022)
"High-spirited heroine Charlotte Heywood ... returns to the picturesque coastal resort of Sanditon and the companionship of her friend Georgiana Lambe ... . What adventures, scandals, intrigue and above all else--romance--await Miss Heywood this season?"--Container.